HUBUNGAN PENAMBAHAN ELEMEN PERADIASI IDENTIK PADA ANTENA MIKROSTRIP ARRAY PATCH BINTANG TERHADAP GAIN, BANDWIDTH, DAN SPECIFIC ABSORPTION RATE PADA FREKUENSI 2.4 GHz - Trystan Nurrahman; Rudy Yuwono; Ali Mustofa (Jurnal Mahasiswa TEUB, 2021)
Abstrak Dalam upaya meningkatkan gain, memperlebar bandwidth, dan mengurangi nilai sar, Makalah ini membahas bagaimana cara mengurangi kelemahan antena mikrostrip yang memiliki mendapatkan dan mempersempit bandwidth, sementara pada saat yang sama memecahkan masalah keamanan bagi pengguna mengenai tingkat penyerapan spesifik, beberapa antena array 1x2, dan 1x4 dirancang, untuk bandingkan hasilnya dengan antena 1x1 tunggal. Untuk menguji nilai sar, benda virtual adalah dirancang dan ditempatkan terpisah 4cm dari antena di aplikasi CST Studio Suite, Dari hasil simulasi didapatkan gain, sar, bandwidth, multiple antenna lebih baik dari antena tunggal, dimana hasil simulasi dari susunan antena 1x4 adalah 5.602dB untuk Penguatan, 0,633 W/Kg untuk SAR, dan 746 MHz untuk Bandwidth.Kata kunci : antena, antena mikrostrip, gain, bandwidth, sar.Abstract In an effort to increase gain, widen the bandwidth, and reduce the sar value, this paper discusses how to reduce the disadvantages of microstrip antennas, which have low gain and narrow bandwidth, while at the same time solving the safety problem for users regarding specific absorption rate, multiple antenna array 1x2, and 1x4 is designed, to compare the results to a single 1x1 antenna. For testing the sar value, the virtual body is designed and placed 4cm apart from the antenna in the CST Studio Suite application, the simulation results obtained, the gain, sar, bandwidth, of multiple antennas are better than the single antenna, where the simulation results from 1x4 antenna array are 5.602dB for Gain, 0.633 W/Kg for SAR, and 746 MHz for Bandwidth. Keywords : antenna, microstrip antenna, gain, bandwidth, sar.Abstract In an effort to increase gain, widen the bandwidth, and reduce the sar value, this paper discusses how to reduce the disadvantages of microstrip antennas, which have low gain and narrow bandwidth, while at the same time solving the safety problem for users regarding specific absorption rate, multiple antenna array 1x2, and 1x4 is designed, to compare the results to a single 1x1 antenna. For testing the sar value, the virtual body is designed and placed 4cm apart from the antenna in the CST Studio Suite application, the simulation results obtained, the gain, sar, bandwidth, of multiple antennas are better than the single antenna, where the simulation results from 1x4 antenna array are 5.602dB for Gain, 0.633 W/Kg for SAR, and 746 MHz for Bandwidth. Keywords:antenna, microstrip antenna, gain, bandwidth, sar.